Addressing the near absence of formal governance in service provision: governance practices thriving in informal settlements - Ivy Chumo; Caroline Kabaria; Rosie Steege; Noemia Teixeira de Siqueira Filha; Alex Shankland; Helen Elsey; Penelope A. Phillips-Howard; Blessing Mberu (Discover Public Health)
Abstract Introduction Service delivery and representation in informal settlements often exhibit a hybrid governance system, encompassing both formal and informal mechanisms. While formal governance structures, such as municipal authorities, are typically emphasized, their absence or inadequacy does not equate to a governance void. Instead, a diverse array of non-state actors, including resident-led initiatives and local service providers, frequently step in to fill the service delivery gaps. These informal actors create a networked governance system through self-organization and collaboration, often responding to the immediate needs of residents. This research aims to uncover and document the nature and dynamics of these informal governance practices within informal settlements in Nairobi, Kenya. By acknowledging and understanding the contributions of these informal actors, we value them and move beyond viewing them as temporary aberrations or unintended consequences of state failure. Methodology This study employed qualitative research methodology, utilizing in-depth interviews with 36 informal service providers operating in the education, healthcare, water, sanitation, and solid waste management sectors. These service providers were selected based on their history of serving vulnerable populations, including older persons, persons with disabilities, and child-headed households, and had been operational for at least eight years. Additionally, four local leaders from two urban informal settlements in Nairobi, Kenya, were interviewed. Data from the transcribed interviews were analyzed using thematic framework analysis, informed by Ostrom’s framework of self-governance, which provides a conceptual lens for understanding the management of common pool resources. Results We identified key crosscutting informal governance strategies in service delivery, including clear boundaries, alignment with local needs, effective resource management, collaborative decision-making, monitoring, appropriate sanctions, conflict resolution, and external recognition. However, challenges such as poor accountability, inadequate leadership, lack of political will, and unclear policies hindered the effectiveness of these informal governance structures. To address these challenges, results uncovered the need to focus on enhancing accountability, strengthening leadership, fostering consensus, clarifying policies, and promoting inclusive participation in service delivery. Conclusion The intricate governance of basic services in informal settlements is largely driven by informal practices and structures. Strengthening these structures alongside recognizing and valuing them is key. By documenting, acknowledging and supporting these informal governance structures, we can create a more equitable and sustainable service delivery systems for residents of informal settlements in Nairobi and beyond.